Implementation Of Occupational Safety and Health (K3) Program At PT Sahung Brantas Energi PLTM In Bungin Tambun, Padang Guci Hulu District (UNIB Press, 2025)
This research is motivated by the lack of implementation of Occupational Safety and Health (K3) at PT.Sahung Brantas Energi PLTM. The purpose of this study is to determine the K3 program at PT. Sahung Brantas Energi PLTM, to determine the Implementation of K3 at PT. Sahung Brantas Energi PLTM, and to determine how accidents and occupational diseases are at PT. Sahung Brantas Energi PLTM. The technique for obtaining data uses observation sheets and interviews with 5 informants including 1 unit leader or manager, 2 coordinators, 1 operator, and 1 security officer. The results obtained from this study regarding the implementation of the Occupational Safety and Health (K3) program at PT. Sahung Brantas Energi PLTM, it can be concluded that this company has a strong commitment to the implementation of K3. The implementation of the K3 program in the company includes integrity in the K3 management system, strict application of PPE, and a comprehensive occupational health program. This program is supported by routine training, periodic evaluations, and supervision to ensure safety standards are met. Although the level of work accidents at PT Sahung Brantas Energi PLTM is relatively low, there are challenges in compliance with the use of PPE, especially during work breaks. Continuous education and strict supervision play an important role in encouraging employee awareness and compliance.